Effect of Exposure Parameters on Metal Artifacts in Cone Beam Computed Tomography - Panjnoush, Mehrdad (J Dent (Tehran), 2016)
OBJECTIVES: The aim of this study was to assess the effect of tube current, kilovoltage peak (kVp), metal type, and the position of metal objects on metal artifacts in cone-beam computed tomography (CBCT) images. MATERIALS AND METHODS: Titanium and cobalt-chromium rods were fabricated and placed in a dry human mandible. Samples were scanned using a Promax 3D CBCT unit with different milli-amperages and kVp. The artifacts induced by metal objects were evaluated using the Image J software in four regions of interest (ROIs) on each image. RESULTS: A higher kVp decreased artifacts of the buccal surface of the rods in 97% of the cases (P=0.046) but did not affect the severity of artifacts between the two metal objects (P>0.05). Increasing the tube current had no effect on metal artifacts in 93% of the cases (P>0.05). Artifacts induced by a cobalt-chromium alloy were more severe than those with titanium (P<0.001). Artifacts were more intense in the buccal surface of anterior rods compared to the posterior rods (P<0.003). CONCLUSIONS: Tube voltage, metal type and the position of metal objects affected the severity of metal artifacts on CBCT images. The metal type had the greatest effect on metal artifact intensity in this study.